Taxonomic delineation of two closely allied Rubus L. (Rosaceae) species with notes on the typification of the name R. fairholmianus - Narayanan, Bhavadas; Prabhukumar, Konickal Mambetta; Kumar, Vannaratta Veetil Naveen; Harinarayanan, C.m.; Chinnappan, Satheshkumar; Umesh, Balakrishnan Thara (Phytotaxa, 2023)
Rubus fairholmianus Gardner and R. micropetalus Gardner are the two closely allied taxa, collected from different localities of southern Western Ghats, India. Because of the absence of detailed description and the existence of morphological similarities, these taxa have been misidentified in many herbaria and other published floras. The present study discusses the major delineating features of both the taxa based on the conventional taxonomic studies and along with seed morphological analysis and also provides a note on the occurrence of R. moluccanus L. in Western Ghats. During the study, the name R. fairholmianus is also neotypified.